Analysis of the Yogurt Nutrient Content and Antioxidant Activity by Adding Podang Urang Mango Juice (Mangifera Indica L.) - Dyah Nurul Afiyah; Riska Nurtantyo Sarbini; M. Shofaul Huda (Jurnal Ternak : Jurnal Ilmiah Fakultas Peternakan Universitas Islam Lamongan, 2022)
Yogurt is a nutrient-rich drink and is mostly liked by many consumers. However, the thermal process in yogurt manufacturing reduces its final product nutrients. Therefore, Podang Urang mango (Mangifera indica l.) juice is added to give the supplementation of the yogurt. This research aims to find out the yogurt nutrient content and antioxidant activity by adding Podang Urang mango juice. There were four different treatments in the process of adding Podang Urang mango juice, there was P0 (0%), P1 (3%), P2 (6%), and P3 (9%). The observed parameter used in this research were the water content, ash, protein, fat, carbohydrate, vitamin C, and antioxidant activity. This result showed that addition Podang Urang mango juice has significantly increased the water content, carbohydrate content, vitamin C, and antioxidant activity. Nonetheless, it has significantly decreased the fat content in yogurt. Whereas, there were no significant differences between the ash content and protein when adding Podang Urang mango juice.